Lactation in yearling Alaskan reindeer: Implications for growth, reproduction, and survival - Prichard, Alexander K.; Finstad, Greg L.; Shain, Drew H. (Rangifer, 1999)
Unlike most Rangifer herds, free-ranging female reindeer Rangifer tarandus) on the Seward Peninsula, Alaska frequently give birth as yearlings (12 months). In other reindeer herds this early reproduction has led to negative effects such as decreased future weight gain and reproduction. We analyzed reindeer data collected on the Seward Peninsula between 1987 and 1997 to determine what effect lactating as yearlings had on future weight gain, reproductive rates, and survival. Reindeer were rounded up during June and early July. Individual ear tag numbers were recorded, females were visually inspected for the presence of a distended udder, and some animals were weighed. Females with distended udders as yearlings had subsequent recapture rates, survival rates, weight gain, and future reproductive success comparable to females that did not have distended udders as yearlings. These findings suggest that the beneficial effects of increased calf weight gain outweigh potential negative effects of early reproduction in these reindeer. This may be due to high quality range leading to heavy calves and the ability of females to maintain body reserves during lactation.